Agriculture and climate change: Mitigating greenhouse gas emissions from livestock systems - Herrero, Mario; Thornton, Philip K. (International Food Policy Research Institute, 2009)
Livestock—poultry, small ruminants (such as goats and sheep), cattle, and pigs—provide many benefits for human well-being. Livestock production systems, especially in developing countries, are changing rapidly in response to population growth, urbanization, and growing demand for meat and milk. The need for action by all sectors to mitigate climate change adds additional complexity to the already considerable development challenges these systems face. Some livestock production systems use large quantities of natural resources and also produce significant amounts of greenhouse gas emissions (GHGs). Since the demand for meat and milk is increasing, the question is whether cost-effective mitigation options exist to meet them within equitably negotiated and sustainable GHG emission targets. In fact, emissions from livestock systems can be reduced significantly through technologies, policies, and the provision of adequate incentives for their implementation. The objective of this policy brief is to highlight options to mitigate GHGs from livestock industries and to suggest key negotiating outcomes for including livestock in the Copenhagen meetings.